2016
DOI: 10.1158/1535-7163.mct-15-0427
|View full text |Cite
|
Sign up to set email alerts
|

Periostin (POSTN) Regulates Tumor Resistance to Antiangiogenic Therapy in Glioma Models

Abstract: Periostin (POSTN) interacts with multiple integrins to coordinate a variety of cellular processes, including epithelial-to-mesenchymal transition (EMT) and cell migration. In our previous study, anti-vascular endothelial growth factor A (VEGF-A) therapy was associated with resistance and EMT. The present study sought to determine the role of POSTN in the resistance of glioma stem cells (GSCs) to antiangiogenic therapy. In mouse xenograft models of human glioma, POSTN expression was associated with acquired res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 49 publications
2
62
0
Order By: Relevance
“…Matsunaga et al reported that periostin was expressed at higher level in primate cerebral cortex than mouse cerebral cortex and periostin exhibited neurite outgrowth activity in brain tissues . Recent studies have revealed that periostin was overexpressed in neural stem cell (NSCs) following hypoxia ischemia and hypoxia could increased periostin expression . Hypoxia, oxidative stress and inflammatory reaction could be involved in the pathological processes of traumatic brain injury (TBI) and stroke, so periostin was supposed to elevated in these neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Matsunaga et al reported that periostin was expressed at higher level in primate cerebral cortex than mouse cerebral cortex and periostin exhibited neurite outgrowth activity in brain tissues . Recent studies have revealed that periostin was overexpressed in neural stem cell (NSCs) following hypoxia ischemia and hypoxia could increased periostin expression . Hypoxia, oxidative stress and inflammatory reaction could be involved in the pathological processes of traumatic brain injury (TBI) and stroke, so periostin was supposed to elevated in these neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In this current study, we investigated the relationship between POSTN expression and bevacizumab resistance in mouse glioma stem cells xenograft tumors. In our model of anti-VEGF-A resistance 3 , GSC11 and U87 tumors treated with bevacizumab expressed higher POSTN levels than control tumors. Periostin (POSTN; osteoblastspecific factor 2) is a 90-kDa ECM protein containing an amino-terminal EMI domain, tandem repeats of four fasciclin domains, and a carboxyterminal (C-terminal) domain, including a heparin binding site 5 .…”
mentioning
confidence: 72%
“…Studies suggest mesenchymal transition and hypoxia signaling as two major pathways associated with the development of resistance to anti-VEGF therapy. Recently, we reported that the glioma treated with bevacizumab have higher periostin (POSTN) expression than control tumors in a murine glioma tumor models 3 . In this commentary, we review our recent findings as well as the role of POSTN in antiangiogenic therapy resistance in glioma.…”
mentioning
confidence: 99%
“…Periostin is a secreted matrix N‐glycoprotein that plays vital roles in numerous cancers, especially in gastrointestinal malignancy . For pancreatic cancer, it is reported that POSTN has a biphasic effect on cell migration and correlates with the epithelial to mesenchymal transition of human pancreatic cancer cells, participates in the process of tumor angiogenesis, and could promote invasiveness and resistance of pancreatic cancer cells to induce cell death .…”
Section: Discussionmentioning
confidence: 99%